Nosocomial Infections in Burned Patients in Motahari Hospital, Tehran, Iran. (14th November 2011) - Azimi, Leila; Motevallian, Abbas; Ebrahimzadeh Namvar, Amirmorteza; Asghari, Babak; Lari, Abdolaziz Rastegar
Abstract : Burn patients are at high risk of developing nosocomial infection because of their destroyed skin barrier and suppressed immune system, compounded by prolonged hospitalization and invasive therapeutic and diagnostic procedures. Studies on nosocomial infection in burn patients are not well described. The objective of the present study was to identify the causative bacterial of nosocomial infection and to determine the incidence of nosocomial infection and their changing during hospitalization in burned patients admitted to in the Motahari Hospital, Tehran, Iran. During the second part of 2010, 164 patients were included in this study. Samples were taken the first 48 hours and the fourth week after admission to Motahari Burn hospital. Isolation and identification of microorganisms was performed using the standard procedure. Of the 164 patients, 717 samples were taken and 812 bacteria were identified, 610 patients were culture positive on day 7 while 24 (17.2%) on 14 days after admission. The bacteria causing infections were 325 Pseudomonas, 140 Acinetobacter, 132 Staphylococcus aureus, and 215 others. The percentage of mortality was 12%. All of patients had at least 1 positive culture with Pseudomonas and/or with Acinetobacter . Hospitals suggest continuous observationof burn infections and increase strategies for antimicrobial resistance control and treatment of infectious complications.